2020
DOI: 10.1002/ppul.24727
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxicity in adult patients with cystic fibrosis using polymyxin B for acute pulmonary exacerbations

Abstract: We present four case reports that describe neurotoxicity experienced in adult patients with cystic fibrosis (CF) receiving intravenous polymyxin B. Paresthesia was observed after the first dose of polymyxin B in all patients. These symptoms resolved after discontinuation of polymyxin B and switching treatment to colistin. All four patients completed therapy with colistin without experiencing additional adverse reactions. This report contributes to the small body of literature currently available on the use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Neurotoxicosis due to polymyxin administration is known in human medicine causing signs such as paresthesia, dizziness, ataxia, and apnea [13,19]. In healthy horses, we recently showed the development of ataxia and weakness due to PolyB administration [23].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Neurotoxicosis due to polymyxin administration is known in human medicine causing signs such as paresthesia, dizziness, ataxia, and apnea [13,19]. In healthy horses, we recently showed the development of ataxia and weakness due to PolyB administration [23].…”
Section: Discussionmentioning
confidence: 99%
“…Paresthesia is the most common sign of neurotoxicosis in humans and abnormal sensatory pathways might also explain ataxia in horses [13,19]. The pathomechanism of PolyB neurotoxicity is incompletely understood; while earlier study suggested a neuromuscular blockade by a reduced sensitivity of the motor end plate to acetylcholine, newer studies show neuronal oxidative stress and mitochondrial dysfunction in response to polymyxin administration in mice [14,20,25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations